2019
DOI: 10.32098/mltj.01.2014.06
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic findings during and after Platelet Rich Plasma injections in tendons

Abstract: Platelet rich plasma has been used in the treatment of tendinopathies, but the sonographic modifications of tendons have received less attention. In this paper we report the results of an ultrasound evaluation, performed during and after plasma injection, in patients with tendinopathy. The sonographic abnormalities and neovascularization were registered in twenty tendons. Three plasma injections (once a week) were performed, and a rehabilitation program was recommended. Pain and patients' satisfaction were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Despite still uncertain steps of PRP effects, in the short-term the factors released by the platelets most likely lower tissue inflammation and modulate the pain receptors sensibility. 23 Afterwards, PRP favors the cell proliferation with collagen and matrix deposition, as well as tissue remodeling. The final outcome is tissue scar formation, which can help to restore tendon function.…”
Section: Discussionmentioning
confidence: 99%
“…Despite still uncertain steps of PRP effects, in the short-term the factors released by the platelets most likely lower tissue inflammation and modulate the pain receptors sensibility. 23 Afterwards, PRP favors the cell proliferation with collagen and matrix deposition, as well as tissue remodeling. The final outcome is tissue scar formation, which can help to restore tendon function.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a higher mechanical load and training load promote collagen synthesis, which is measurable using SWE [47]. This may explain the higher patellar tendon stiffness in male athletes because of a higher mechanical load due to higher body mass and muscle strength; however, no professional athletes were included in these studies [4,48]. Another explanation could be the effect of female hormones on collagen synthesis.…”
Section: Influence Of Physical Parameters On Patellar Tendon Stiffnessmentioning
confidence: 99%
“…In these two studies, there was a reduction in neovascularization. The explanation for use of PRP in injured tissues is given by their likely ability to provide beneficial hyperphysiological doses of growth factors to the tissue (3,27) . The use of PRP is increasing in order to aid in the repair process in tendons, although its effects are poorly understood and some studies have not observed a better PRP effect when compared to eccentric exercise.…”
Section: Vascularizationmentioning
confidence: 99%